Fishermen Follow Fine-Scale Physical Ocean Features for Finance - Watson, James R.; Fuller, Emma C.; Castruccio, Frederic S.; Samhouri, Jameal F. (Frontiers in Marine Science, 2018)
The seascapes on which many millions of people make their living and secure food have complex and dynamic spatial features – the figurative hills and valleys – that influence where and how people work at sea. Here, we quantify the physical mosaic of the surface ocean by identifying Lagrangian Coherent Structures for a whole seascape – the U.S. California Current Large Marine Ecosystem – and assess their impact on the spatial distribution of fishing. We observe that there is a mixed response: some fisheries track these physical features, and others avoid them. These spatial behaviors map to economic impacts, in particular we find that tuna fishermen can expect to make three times more revenue per trip if fishing occurs on strong Lagrangian Coherent Structures. However, we find no relationship for salmon and pink shrimp fishing trips. These results highlight a connection between the biophysical state of the oceans, the spatial patterns of human activity, and ultimately the economic welfare of coastal communities.